GPATCH3, a splicing regulator that facilitates tumor immune evasion via the modulation of ATPase activity of DHX15 - Ren, Tingrong; Wei, Gaigai; Yi, Jingjing; Zhang, Yuqi; Zhao, Haiping; Wu, Nana; Zhang, Huiling; Guo, Zhihan; Wang, Yihan; Kuang, Jiating; Sheng, Zhaoying; Zhang, Duanwu (Frontiers in Immunology, 2025)
IntroductionAberrant pre-mRNA splicing is increasingly recognized as a key contributor to tumorigenesis and immune evasion. However, the regulatory factors orchestrating splicing dynamics within the tumor microenvironment (TME) remain incompletely understood. Here, we identify GPATCH3, a previously uncharacterized G-patch domain–containing protein, as a critical modulator of alternative splicing and immune regulation in cancer.MethodsWe employed biochemical studies, splicing reporter assays, and transcriptomic analyses to elucidate the function of GPATCH3. In vitro and in vivo models, including GPATCH3-depleted cell lines and mouse xenografts, were used to assess its roles in tumor progression. Immune infiltration patterns were analyzed using TIMER2.0 based on TCGA transcriptomic data.ResultsGPATCH3 interacts with the RNA helicase DHX15 and enhances its ATPase activity, promoting proper spliceosome disassembly. Loss of GPATCH3 led to splicing alterations, including in immunoregulatory genes such as CXCR3, CD44, and FOXP3. Functional studies revealed that GPATCH3 deficiency attenuated tumor growth in vivo. Conversely, elevated GPATCH3 expression was associated with reduced infiltration of cytotoxic T cells and NK cells, alongside an enrichment of immunosuppressive populations such as MDSCs and CAFs across multiple cancer types. Transcriptomic analysis further revealed that GPATCH3 deficiency upregulates immunomodulatory genes such as CXCL8 and LAG3, suggesting a role in shaping the TME via splicing regulation.DiscussionOur findings suggest GPATCH3 as a critical regulator that governs alternative splicing and immunosuppressive microenvironment remodeling. By modulating the splicing fidelity of key immune genes and altering their expression, GPATCH3 may facilitate immune escape and tumor progression. These results provide mechanistic insights into how RNA splicing factors interface with immune regulation and highlight GPATCH3 as a potential therapeutic target for immunomodulatory cancer therapy.